Discontinuous carbon fibre composites for automotive applications - Harper, Lee Thomas (2006)
Increasingly stringent emissions targets are encouraging vehicle manufacturers to prioritise reduction of vehicle mass. The falling cost of carbon fibre is increasing the viability of lightweight carbon-based body panel systems across a broad range of production volumes. In the present work an automated process has been developed for the manufacture of random fibre preforms at medium volume production levels (30-50,000ppa).